The Dynamics of Identity Politics In Indonesia: A Study of Nurcholish Madjid's - Donna Ramadhan Fitri; Miswardi Miswardi; Ferdi Yufriadi; Irvan Refliandi; Syafriadi B (Alhurriyah, 2023)
Islamic political power is not always related to Islamic parties. Nurcholish Madjid tried to convey a more substantial view of Islam, not just symbolism. This research uses the library research method. Research carried out using literature, both in the form of primary sources, namely research data sources obtained from original sources that contain this information and secondary sources, namely data sources obtained from books and other literature that discuss the topic of the problem. The data processing techniques in this study using content analysis techniques, namely after the data is collected, the next step is to describe the data completely, sequentially, and regularly, and after that the analysis is carried out by looking at each discussion of the themes discussed. Based on the results of this research, it is revealed that Nurcholish Madjid chose Islam that is more substantial than just symbolism. This is rooted in the universal values of Islam, not just the symbol of the "Islamic party" itself. If we look at the current situation, Nurcholish Madjid's criticism is still relevant because currently the politicisation of religion is generally used to attack political opponents or increase party electability.Kekuatan politik Islam tidak selalu berkaitan dengan partai Islam. Nurcholish Madjid mencoba menyampaikan pandangan yang lebih substansial tentang Islam, bukan sekedar simbolisme. Penelitian ini menggunakan metode penelitian kepustakaan (library reseach). Penelitian yang dilaksanakan dengan menggunakan literatur (kepustakaan), baik berupa dari sumber primer yaitu sumber data penelitian yang diperoleh dari sumber-sumber asli yang memuat informasi tersebut dan sumber sekunder yaitu sumber data yang diperoleh dari buku dan literatur lain yang membahas tentang topik permasalahan. Adapun teknik pengolahan data dalam penelitian ini dengan menggunakan teknik content analisis, yaitu setelah data-data tersebut terkumpul, maka langkah selanjutnya adalah memaparkan data tersebut secara lengkap, urut, dan teratur, dan setelah itu dilakukan analisis dengan mencermati setiap pembahasan tema yang dibahas. Berdasarkan hasil penelitian ini, terungkap bahwa Nurcholish Madjid memilih Islam yang lebih substansial dari sekedar simbolisme. Hal ini berakar pada nilai-nilai universal Islam, bukan hanya simbol "partai Islam" itu sendiri. Jika melihat situasi saat ini, kritik yang dilontarkan Nurcholish Madjid masih relevan karena saat ini politisasi agama umumnya digunakan untuk menyerang lawan politik atau meningkatkan elektabilitas partai.